Understanding passing network characteristics and their link to match outcome in elite Netball - Young, C.; Bruce, L.; Dwyer, D.; Di Domenico, I.; Fox, A. (Journal of Sports Sciences, 2023)
Player interactions in Netball are critical during attacking phases of play to ensure possession is maintained and scoring opportunities are created. This study aims to analyse the characteristics of the passing networks of elite Netball teams and their association with performance outcomes (i.e., win/loss and final margin). Five network metrics used to represent the characteristics of teamwork were calculated for all team performances (n = 112) from one season of professional Netball in Australia. A two-way ANOVA and multiple linear modelling were used to compare characteristics between teams and match outcomes and to predict score margin, respectively. Pass density (F = 65.09, df = 102, p < .001) and pass centrality (F = 7.61, df = 102, p < .01) differed (were higher) in wins/losses. They were also statistically significant contributors (p = .005) to the linear model that predicted a score margin (R2 = .731). Key player centrality and mutual connectedness were different between teams but did not differ by match outcome. The results suggest that, ideally, Netball teams should maximise the number of connections between player pairings, while also relying on a subset of players to be heavily involved in passing sequences. Team cohesion (via passing) therefore appears to be an important measure of team success in elite Netball.